MINAT BACA ANAK – ANAK DESA ULAK SEGELUNG KECAMATAN INDRALAYA KABUPATEN ORGAN ILIR - Isnaria, Mefhi (Jurnal Pengabdian Masyarakat Berkarya, 2024)
This PKM activity aims to foster the reading interest of elementary school students SD Negeri 09 indralaya ulak segelung village organ ilir district, reading plays a very important social role in human life. The more content a person reads, the wider the scope of his thinking. The problem that arises is the lack of student interest in reading to support reading instruction. This is due to students' lack of understanding of the text to be read and lack of vocabulary mastery, including not knowing how to read correctly in accordance with the objectives to be achieved. This research method is a direct approach with the research location observation method. The type of data is qualitative data or in descriptive form, the data source is primary data. The result of this service is that students' interest in reading today cannot be said to be adequate in supporting the smooth teaching of reading. Starting from this fact, the author tries to deliver several possible teacher efforts in increasing students' interest in reading.